Pengabdian kepada Masyarakat: Perkembangan dan Pertumbuhan Iman pada Pemuda dan Remaja Setelah Pemuridan di Gereja Protestan Persekutuan (GPP) Siaro - Geovando Siahaan; Asima Putri Handayani Nababan; Rina Fretti Manalu; Yenima Clarisa Simanjuntak; Adi Suhenra Sigiro (Jurnal DIKMAS, 2024)
This research aims to analyze the development and growth of faith in youth and teenagers after implementing discipleship and teaching at the Siaro Fellowship Protestant Church (GPP) for two months. This discipleship activity is carried out by intern students from the Theology Study Program every night of the week with material that includes an introduction to Jesus, His humanity and divinity, divine character, the work of Jesus Christ, death and His ascension. The research method used is a qualitative approach with in-depth interviews and participant observation. The research results show that this discipleship program has succeeded in increasing theological understanding, deepening personal relationships with Jesus, and strengthening faith commitment among youth and teenagers. Apart from that, this activity also encourages active participation in church activities and community service.